TET2 is required to suppress mTORC1 signaling through urea cycle with therapeutic potential - Jing He; Mingen Lin; Xinchao Zhang; Ruonan Zhang; Tongguan Tian; Yuefan Zhou; Wenjing Dong; Yajing Yang; Xue Sun; Yue Dai; Yue Xu; Zhenru Zhang; et al. (Cell Discovery, 2023)
Abstract Tumor development, involving both cell growth (mass accumulation) and cell proliferation, is a complex process governed by the interplay of multiple signaling pathways. TET2 mainly functions as a DNA dioxygenase, which modulates gene expression and biological functions via oxidation of 5mC in DNA, yet whether it plays a role in regulating cell growth remains unknown. Here we show that TET2 suppresses mTORC1 signaling, a major growth controller, to inhibit cell growth and promote autophagy. Mechanistically, TET2 functions as a 5mC “eraser” by mRNA oxidation, abolishes YBX1–HuR binding and promotes decay of urea cycle enzyme mRNAs, thus negatively regulating urea cycle and arginine production, which suppresses mTORC1 signaling. Therefore, TET2-deficient tumor cells are more sensitive to mTORC1 inhibition. Our results uncover a novel function for TET2 in suppressing mTORC1 signaling and inhibiting cell growth, linking TET2-mediated mRNA oxidation to cell metabolism and cell growth control. These findings demonstrate the potential of mTORC1 inhibition as a possible treatment for TET2-deficient tumors.